2022
DOI: 10.3390/biomedicines10071542
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Growth and Differentiation in Organ Culture: New Insights for Uterine Fibroid Treatment

Abstract: Organ culture allows for the understanding of normal and tumor cell biology, and tissues generally remain viable for 5–7 days. Strikingly, we determined that myometrial and MED12 mutant leiomyoma cells repopulated cell-depleted tissue slices after 20 days of culture. Using immunofluorescence and quantitative PCR of stem cell and undifferentiated cell markers, we observed clusters of CD49b+ cells in tumor slices. CD49b+ cells, however, were sparsely detected in the myometrial slices. Almost all LM cells strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Despite their high prevalence, up to 70% of fibroids are asymptomatic and thus do not require frequent follow-up or medical intervention ( 8 ). The differences in the sizes and locations of fibroids can lead to different clinical symptoms, with 15–30% of patients experiencing severe symptoms ( 18 ), such as abnormal uterine bleeding, dysmenorrhea, urinary frequency or constipation, sexual dysfunction, and infertility, which impair their physical and mental health ( 19 ). Although UFs are benign tumors, there is also a possibility of malignant transformation, and the malignancy rate of patients with UFs is about 0.5% in China and about 0.13–1.0% in foreign countries.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their high prevalence, up to 70% of fibroids are asymptomatic and thus do not require frequent follow-up or medical intervention ( 8 ). The differences in the sizes and locations of fibroids can lead to different clinical symptoms, with 15–30% of patients experiencing severe symptoms ( 18 ), such as abnormal uterine bleeding, dysmenorrhea, urinary frequency or constipation, sexual dysfunction, and infertility, which impair their physical and mental health ( 19 ). Although UFs are benign tumors, there is also a possibility of malignant transformation, and the malignancy rate of patients with UFs is about 0.5% in China and about 0.13–1.0% in foreign countries.…”
Section: Discussionmentioning
confidence: 99%
“…Another work conducted by Salas and colleagues observed that myometrial and MED12 mutant leiomyoma cells repopulated cell-depleted tissue slices after 20 days of culture. They detected clusters of CD49b+ cells in tumor slices using immunofluorescence and quantitative PCR of stem cell and undifferentiated cell markers [50]. However, there were only a few CD49b+ cells found in the myometrial slices.…”
mentioning
confidence: 99%